A qualitative study on perspectives of pregnant and postnatal mothers on accessing Tetanus Toxoid vaccine in Hai District Kilimanjaro region Tanzania - Asia Hemed Kipengele; Sweetness Naftal Laizer; Perry M Cyril; Zuhura Lintu; Nateiya M Yongolo; Neema Allen Ng'unda; Irene Haule; Blandina Theophil Mmbaga; Agnes Cyril Msoka (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2021)
Background: Antenatal care for pregnant and postnatal mothers is the main entry gate for maternal Tetanus Toxoid (TT) vaccination. In developing countries including Tanzania, pregnant and postnatal mothers especially in rural communities have been experiencing barriers to maternal vaccination. The study aimed to explore perspectives of pregnant and postnatal mothers on accessing TT vaccine in Hai District Kilimanjaro Region Tanzania. Methods: A descriptive qualitative study was conducted during baseline assessment from October 2020 to May 2021, in 10 remote villages. Pregnant and postnatal mothers attending antenatal and postnatal services were selected purposively based on their availability and convenience, A semi-structured interview guide relevant to the study objectives was used to guide the interviews. Focus Group Discussion (FGD) and In-depth interviews (IDIs) were conducted; and thematic analysis was used to obtain themes and subthemes. Results: A total of 15 mothers aged 18 to 40 years participated in the study. Most of the mothers were Christians, married with 1 to 5 children. Majority had completed primary level education engaged in small-scale farming. Main themes were extracted namely: Unreliable vaccine information, Healthcare workers attitude, Overworked with household activities, adherence of appointment dates for vaccination after delivery and role of Traditional medicine during pregnancy. Conclusion: The role of healthcare providers are critical component for the appropriate transfer of vaccine information to the mothers and their spouses during clinic visits, to eliminate vaccine misconceptions hence improving overall tetanus vaccine uptake. Quality of information from reliable sources could be an important factor to upgrade the awareness of pregnant mothers on maternal vaccination.